Development and validation of laboratory procedures for preimplantation diagnosis of Duchenne muscular dystrophy. Issue 11 (November 1993) - Holding, C; Bentley, D; Roberts, R; Bobrow, M; Mathew, C
Abstract : In order to develop and validate methods for the preimplantation diagnosis of Duchenne muscular dystrophy (DMD), we have established and evaluated PCR assays for the analysis of four loci within the DMD gene and for two Y chromosome sequences in single cells. A model system using buccal cells picked from mouthwash samples has been used for an extensive evaluation of the sensitivity and specificity of the assays, and each assay has been tested in samples containing single cells, two cells, and three cells per tube. The four DMD and two Y assays have been combined in duplex and triplex reactions to enable simultaneous diagnosis of DMD and of fetal sex. One of the DMD markers is a highly polymorphic simple tandem repeat locus which produces a basic DNA profile, and provides a control for contamination by foreign DNA. Amplification of DMD or Y sequences was observed in 78 to 92% of single male cells, rising to 96% and 97% in tubes containing two or three male cells respectively. Coamplification of both a DMD and a Y sequence together occurred with a mean success of 74% in single male cells, increasing to 93% with two, and 95% with three cells per tube. With appropriate precautions, we believe that it is now possible to proceed to clinical application of these procedures.